ETV6 Gene Rearrangements Characterize a Morphologically Distinct Subset of Sinonasal Low-grade Non–intestinal-type Adenocarcinoma: A Novel Translocation-associated Carcinoma Restricted to the Sinonasal Tract. (November 2017) - Andreasen, Simon; Skálová, Alena; Agaimy, Abbas; Bishop, Justin A.; Laco, Jan; Leivo, Ilmo; Franchi, Alessandro; Larsen, Stine R.; Erentaite, Daiva; Ulhøi, Benedicte P.; von Buchwald, Christian; Melchior, Linea C.; et al.
Abstract : Low-grade sinonasal adenocarcinomas (low-grade SNACs) of the sinonasal tract comprise a poorly characterized and histologically heterogeneous group of tumors. We describe three cases of a histologically distinct variant of low-grade SNAC characterized by ETV6 gene rearrangements. The patients included 2 women (aged 32 and 88 y) and a man (aged 75 y); all were initially treated with surgery alone. Follow-up ranged from 9 to 170 months with one patient having 2 local recurrences and none experiencing distant or regional metastases. Tumors were composed of cytologically bland columnar and cuboidal eosinophilic tumor cells with basally located nuclei arranged in tubular and tubulotrabecular patterns. Immunohistochemically, CK7, DOG1, GCDFP-15, and SOX10 were positive in all cases, and vimentin was positive in 2 cases. Scattered single cells or small groups of tumor cells were S-100 positive. Only one case had weak, focal expression of GATA3, and mammaglobin was consistently negative. Two cases had ETV6 - NTRK3 gene fusions, whereas ETV6 had an unknown fusion partner gene in one case. The highly similar morphology, immunohistochemical profile, and genetics of the presented cases are suggestive of a specific disease. Although translocation-associated adenocarcinomas in the sinonasal tract have previously been described exclusively as salivary-type carcinomas, we present the first type of carcinoma characterized by recurrent genetic rearrangements and distinct phenotype occurring exclusively in the sinonasal tract with no known major salivary gland counterpart. We provisionally designate this tumor ETV6 -rearranged low-grade SNAC. Identification of additional cases is necessary to fully appreciate the morphologic and biological spectrum of this disease.